A colorimetric chemosensor based on a Nozoe azulene that detects fluoride in aqueous/alcoholic media - Murfin, Lloyd C. (2020)
Colorimetry is an advantageous method for detecting fluoride in drinking water in a resource-limited context, e. g., in parts of the developing world where excess fluoride intake leads to harmful health effects. Here we report a selective colorimetric chemosensor for fluoride that employs an azulene as the reporter motif and a pinacolborane as the receptor motif. The chemosensor, NAz-6-Bpin, is prepared using the Nozoe azulene synthesis, which allows for its rapid and low-cost synthesis. The chemosensor gives a visually observable response to fluoride both in pure organic solvent and also in water/alcohol binary solvent mixtures.